2009
DOI: 10.1002/ajim.20673
|View full text |Cite
|
Sign up to set email alerts
|

Job strain and the risk for occupational injury in small‐ to medium‐sized manufacturing enterprises: A prospective study of 1,209 Korean employees

Abstract: Background The aim of this study was to investigate whether job strain had an effect on the risk of occupational injury of workers at small‐ to medium‐sized manufacturing companies. Methods We conducted a prospective follow‐up survey and finally 1,209 workers in South Korea were included in this study. At time X1, we measured job stress with the Job Demand and Decision Latitude Questionnaire; and at time X2 (after 6 months), we evaluated occupational injuries through a single question. Occupational injuries we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 27 publications
8
39
1
Order By: Relevance
“…In addition, several studies have indicated that mental health disorders and other potentially associated health problems, such as being overweight or obese, may be risk factors for unintentional injuries, including occupational ones. 5,[25][26][27] The likely bidirectional nature of the relationship between depression and occupational injury may invite the suggestion of reverse causation. We have made efforts to avoid observing reverse causation in this study by restricting the data set to workers without outpatient visits for depression during the previous 3 months.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, several studies have indicated that mental health disorders and other potentially associated health problems, such as being overweight or obese, may be risk factors for unintentional injuries, including occupational ones. 5,[25][26][27] The likely bidirectional nature of the relationship between depression and occupational injury may invite the suggestion of reverse causation. We have made efforts to avoid observing reverse causation in this study by restricting the data set to workers without outpatient visits for depression during the previous 3 months.…”
Section: Discussionmentioning
confidence: 96%
“…23,24 The costs of occupational stress are high due to increased absenteeism and occupational injury. 25,26 Female medical professionals have the difficulties in balancing a job and family responsibilities. They are a special group that is at a higher risk of suffering from occupational stress, as well as job burnout, 2 which leads to a reduced QOL.…”
Section: Commentmentioning
confidence: 99%
“…Studies carried out following publication of this review have shown an increase in the risk of suffering an OI due to various stress factors, such as working hours,11 time pressure,12 high levels of stress at work,13 14 high demands,15 16 low social support,16–18 ambiguity of roles,14 low decision latitude,19 low skill discretion,19 monotonous work,19 interpersonal conflicts at work,19 20 a highly variable workload 16 or insecurity about the job future 16. Several of these studies have also identified gender differences in the association between stress and OI, but the specific pattern of association among gender, job stress and OI has not yet been clarified 18 19 21…”
Section: Introductionmentioning
confidence: 99%
“…This presents a threat to internal validity, since workers who have suffered an OI may systematically report higher stress levels 23. Some studies have focused on very different cultural and economic contexts,20–22 and have generally tended to concentrate on specific sectors rather than exploring the association in a wider sample in which all occupations are represented 16 18 20. Other studies have presented limitations, such as small sample size,12 or a low response rate 15.…”
Section: Introductionmentioning
confidence: 99%